Lasmiditan for the treatment of migraine. (1st February 2017) - Capi, Matilde; de Andrés, Fernando; Lionetto, Luana; Gentile, Giovanna; Cipolla, Fabiola; Negro, Andrea; Borro, Marina; Martelletti, Paolo; Curto, Martina
ABSTRACT: Introduction : Migraine is one of the most common diseases in the world, with high economical and subjective burden. Migraine acute therapy is nowadays based on specific and non-specific drugs but up to 40% of episodic migraineurs still have unmet treatment needs and over 35% do not benefit from triptans administration. Serotonin-1F receptors have been identified in trigeminal system and became an ideal target for anti-migraine drug development as potential trigeminal neural inhibitors. Lasmiditan, a novel serotonin1F receptor agonist, showed specific affinity in vitro for the receptor without any vasoconstrictive action and inhibited markers associated with electrical stimulation of trigeminal ganglion in migraine animal models. Areas covered : This article reviews both preclinical and clinical studies on lasmiditan as a potential acute therapy for migraine, as well as pharmacokinetic and pharmacodynamic features. It also summarizes safety and tolerability data gathered in the various human studies. Expert opinion : The absence of vasoconstrictive effects makes lasmiditan a promising novel migraine acute therapy. Although preclinical and Phase I and II studies established a significant efficacy, the limited knowledge about pharmacokinetics and metabolism, the high rate of non-serious central nervous system side effects and the lack of larger studies remain still a matter of concern that should be addressed in future studies.